Utility of serum immunoglobulin A antibody against glycopeptidolipid core antigen in the diagnosis and management of hypersensitivity pneumonitis associated with Mycobacterium avium complex: A case report. (2023) - Mori, Yuta; Nakashima, Harunori; Funasaka, Takashi; Hori, Sho; Kagajo, Michiko; Abe, Takashi; Ando, Morihide; Shindoh, Joe
Abstract: Measurement of the levels of serum immunoglobulin A antibody against glycopeptidolipid (GPL) core antigen, a cell surface antigen found in Mycobacterium avium complex (MAC), has been reported to be useful in the diagnosis and management of pulmonary MAC infection. However, evidence on its utility in hypersensitivity pneumonitis (HP) associated with MAC (i.e., "hot-tub lung") is limited. We herein report a case of HP associated with MAC in which the GPL core antibody levels were serially measured from diagnosis to treatment and thereafter. A 61-year-old man was suspected to have non-fibrotic HP based on the clinical course, laboratory findings, imaging pattern, bronchoalveolar lavage (BAL) lymphocytosis, and histopathological findings. Based on the history of whirlpool bath use, inhalation of aerosolized MAC was suspected as the cause of HP. The GPL core antibody level, measured using an enzyme-linked immunosorbent assay kit, was elevated, suggesting an immunological sensitization to MAC. A provocation test using the patient's whirlpool bath was positive. An identical MAC strain was isolated from the BAL fluid and bathtub. Accordingly, the patient was diagnosed with HP caused by the inhalation of aerosolized MAC from the whirlpool bath. The patient recovered after steroid treatment and discontinuation of the whirlpool bath. The GPL core antibody levels decreased with disease improvement. In conclusion, GPL core antibody levels could be elevated in HP associated with MAC and decrease with disease improvement. Thus, measurement of the GPL core antibody level may be useful for the diagnosis and management of HP associated with MAC.